Molecular epidemiology and drug resistant mechanism in carbapenem-resistant Klebsiella pneumoniae isolated from pediatric patients in Shanghai, China - Zhang, Xingyu (PLoS One, 2018)
Infection by carbapenem-resistant Klebsiella pneumoniae (CR-KP) is a public health challenge worldwide, in particular among children, which was associated with high morbidity and mortality rates. There was limited data in pediatric populations, thus this study aimed to investigate molecular epidemiology and drug resistant mechanism of CR-KP strains from pediatric patients in Shanghai, China. A total of 41 clinical CR-KP isolates from sputum, urine, blood or drainage fluid were collected between July 2014 and May 2015 in Shanghai Children's Medical Center. Multilocus sequence typing (MLST), antibiotic susceptibility testing, PCR amplification and sequencing of the drug resistance associated genes were applied to all these isolates. MLST analysis revealed 16 distinct STs identified within the 41 isolates, among which the most frequently represented were ST11(19.5%),ST25(14.6%),ST76(14.6%),ST37(9.8%).One new ST was first identified. All CR-KP isolates showed MDR phenotypes and were resistance to ceftazidime, imipenem, piperacillin / tazobactam, ceftriaxone, ampicillin /sulbactam, aztreonam. They were confirmed as carbapenemase producer, NDM-1 (56.1%, 23/41), IMP (26.8%, 11/41), KPC-2 (22.0%, 9/41) were detected. Of note, two isolates carried simultaneously both NDM-1 and IMP-4. All CR-KP strains contained at least one of extended spectrum β-lactamase genes tested(TEM, SHV, OXA-1, CTX-M group) and six isolates carried both ESBL and AmpC genes(DHA-1). Among the penicllinase and β-lactamase genes, the most frequently one is SHV(92.7%,38/41), followed by TEM-1(68.3%,28/41), CTX-M-14(43.9%,18/41), CTX-M-15(43.9%,14/41), OXA-1(14.6%,6/41). In the present study, NDM-1-producing isolates was the predominant CR-KP strains in children, follow by IMP and KPC-producing strains. NDM-1and IMP-4 were more frequent than KPC-2 and showed a multiclonal background. Those suggested carbapenem-resistant in children is diverse, and certain resistance mechanisms differ from prevalent genotypes in adults in the same region. Knowledge of the molecular epidemiology and drug resistant mechanism of CR-KP can have a profound effect on clinical treatment, infection control measures and public health policies for children.